Improving Reading TOEFL Score through Note Taking Strategy - Nyak Mutia Ismail; Ika Apriani Fata (Institut Agama Islam Negeri Imam Bonjol Padang, 2021)
There are still a number of less skilled readers in higher degree education where academic texts are staple needs (Hellekjaer, 2009). This study investigated a technique to help students increase their reading ability in TOEFL reading section. A technique named Notetaking technique was implemented during two cycles of classroom action research. There were 3 meetings for each cycle. The participants were 17 Economics students who are taking TOEFL Preparation course at Universitas Syiah Kuala, Aceh, Indonesia. The result from cycle one showed no increase since the average only incline to 38.58. Then in cycle 2, there was a significant increase reaching 45.11 (which is the minimum TOEFL standard for the university). It can be deduced that this technique might not be appropriate for large classes as it demands individual assistance. Besides, a good skill of organizing information is fundamental in this strategy to maximize the students’ effort in answering the TOEFL questions during the test.